2016
DOI: 10.1080/15287394.2016.1193114
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of testosterone on cognitive dysfunction in Alzheimer’s disease model rats induced by oligomeric beta amyloid peptide 1-42

Abstract: Cognitive dysfunction is known to be influenced by circulating sex steroidal hormones. The aim of this study was to examine the protective effect and possible protective mechanism of testosterone (T) on cognitive performance in male rats induced by intrahippocampal injections of beta amyloid 1-42 oligomers (Aβ1-42). Treatment with T as evidenced by the Morris water maze (MWM) test significantly shortened escape latency and reduced path length to reach the platform compared to the control (C). During probe tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…SYN is a glycoprotein that is located on the membranes of presynaptic vesicles, and SYN expression can accurately and objectively reflect the distribution and density of synapses ( 59), since SYN is closely associated with synapse formation and reconstruction (60). The degree of cognitive decline in animal models of AD has been correlated with changes in SYN expression in the hippocampus (17,(61)(62)(63)(64). The present study demonstrated that EE exposure increased the expression of SYN in the hippocampal CA1 region, which further indicates that EE exposure was able to increase neuronal synapses and improve synaptic plasticity in SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%
“…SYN is a glycoprotein that is located on the membranes of presynaptic vesicles, and SYN expression can accurately and objectively reflect the distribution and density of synapses ( 59), since SYN is closely associated with synapse formation and reconstruction (60). The degree of cognitive decline in animal models of AD has been correlated with changes in SYN expression in the hippocampus (17,(61)(62)(63)(64). The present study demonstrated that EE exposure increased the expression of SYN in the hippocampal CA1 region, which further indicates that EE exposure was able to increase neuronal synapses and improve synaptic plasticity in SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences have reported that age‐related decrease in serum androgen in men facilitates the development of AD pathology and Aβ deposition, which may be conducive for their vulnerability to AD (Götz et al, ; Hardy & Higgins, ; Huo et al, ). However, the factors underlying the AR‐mediated regulation of APP and Aβ remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly the steroid-hormone testosterone-activated transcription factor-signaling AR (ANDR) is known to exert regulatory effects on synaptic plasticity and improve cognitive deficits in AD patients and transgenic rodent models for AD (TgAD) but the underlying mechanisms of androgenic action on cognitive performance remain unclear. Testosterone, via the AR, increases synaptophysin expression and improves synaptic plasticity and cognitive metrics in both Aβ42 peptide-hippocampal injected male rats and in the senescence-accelerated mouse prone 8 (SAMP8) TgAD murine model (Huo et al, 2016; Jia et al, 2016). In a recent double-blind, placebo-controlled, between-subject designed study, exogenous administration of testosterone to healthy adult men potentiated the AR-enriched hippocampus, amygdala and hypothalamus—anatomical regions known to be involved in the stimulation of aggressive behavior (Carré et al, 2016).…”
Section: Discussionmentioning
confidence: 99%